PERSONALITY QUALITIES DEVELOPMENT OPPORTUNITIES IN EXTENDED CHOIR ACTIVITIES - Vitols, Edgars (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The article covers the possibilities to diversify the choir rehearsals and concerts in order to improve the student's emotional intelligence, without the decrease in artistic quality. In this study the authors objective is to create methods for working with the choir, that alongside with the current activity also includes the synchronous, authentic, scenic movement and drama elements for choir rehearsals and concerts. The result of this is the enhancement of the interest in the subject, creation of inspiring working conditions, possibility to socialize, therefore leading to fulfillment of the main objective – the improvement of emotional intelligence.  Based on the opinions of theoreticians and industry experts, it concluded that emotional intelligence is a crucial factor for success in all areas of life. Developing one's emotional intelligence is important for anyone, but especially – the teenagers during the period of personality formation. The conclusions of this study can be used in the work with any choir collective. They are equally adaptable to youth, women's and men's choirs.